2018
DOI: 10.1556/066.2018.47.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Sensory evaluation and electronic tongue for sensing grafted and non-grafted watermelon taste attributes

Abstract: The objective of our study was to analyse the results of two measuring methods (sensory evaluation and electronic tongue) and to fi nd differences in taste between grafted and non-grafted watermelon fruit. The trained sensory panel evaluated in two years three differently treated watermelon fruit. The studied fruit samples were produced on the same growing-areas in both years but with different growing technologies. The experiment used the non-grafted/ self-rooted watermelon as control sample, while the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Sensory results of storage data sets showed significant differences in eight parameters from the ten between grafted and self-root melons (Figure 2c,d), and these two types also could be distinguished from each other based on the results of the electronic tongue and NIRS (Table 6). The results obtained for classification of grafted and self-rooted melons with the electronic tongue are better than obtained for previous studies for watermelons, where technological and environmental conditions had a higher role in the differentiation of samples [21]. It is also true for the melons stored at 2 °C, showing that the electronic tongue is in accordance with the results of the sensory test (Table 6).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Sensory results of storage data sets showed significant differences in eight parameters from the ten between grafted and self-root melons (Figure 2c,d), and these two types also could be distinguished from each other based on the results of the electronic tongue and NIRS (Table 6). The results obtained for classification of grafted and self-rooted melons with the electronic tongue are better than obtained for previous studies for watermelons, where technological and environmental conditions had a higher role in the differentiation of samples [21]. It is also true for the melons stored at 2 °C, showing that the electronic tongue is in accordance with the results of the sensory test (Table 6).…”
Section: Discussionsupporting
confidence: 45%
“…Electronic tongues were applied in several fields of food studies, for instance, classification of different varieties of fruits and vegetables, testing the authenticity of foods and beverages [18,19] or predicting sweetness and sugar content [20]. Hungarian researchers could discriminate regions of watermelon samples based on the results of the electronic tongue [21]. The electronic tongue was also used for discriminate between different processes [22] or storage conditions [18].…”
Section: Introductionmentioning
confidence: 99%
“…Grieneisen et al [15] conducted a review of 202 different rootstocks and 1023 experimental treatments related to tomato grafting, and they concluded that fruit quality data based on sensory tests were rare among the published studies. Sensory evaluation of grafted plants of the members of the Cucurbitaceae family, i.e., melon [16], watermelon [17,18], and cucumber [19], and those of the Solanaceae family [20,21] have been conducted, but there is relatively few data for eggplant.…”
Section: Introductionmentioning
confidence: 99%
“…To expand this knowledge, grafted and nongrafted watermelons grown in different regions of Hungary (Békés, Jász-Nagykun-Szolnok, Fejér county) were analyzed with potentiometric E-tongue (seven ISFET sensors) to predict characteristic sensory attributes, concerning color, texture, juiciness, global scent, and taste. The results revealed that the cultivation circumstances determine mostly the quality factors, not the type of grafted rootstock [ 260 ]. Orange and green-fleshed melons were also studied using the same instrument when the effect of grafting and storage conditions on chemical composition and sensory profile were evaluated.…”
Section: Electronic Tongue: Historical Background and Food Qualitymentioning
confidence: 99%